PENERAPAN APLIKASI SISTEM STOK BARANG DAN KEUANGAN PADA APOTEK SANA FARMA SEMARANG - Priyadi Priyadi; Diyas Adikrisna (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2021)
The application of stock and financial systems in the world of health is needed today, especially interms of buying and selling is an important factor, because with an information system these activities canrun more effectively. Apotek Sana Farma which is located at Jalan Kedung Jati Number 26 Semarang is asupporting agency in terms of health services, especially accommodating the need for goods (drugs) thatare demanded to be fast and precise in serving consumers (patients). To achieve this goal, it is necessary toprepare human resources who are able to accommodate and adapt to the development of science andtechnology, by providing up to date information on health services, accommodating the need for drugs andfinancial information to those in need.In designing a multiuser-based stock and financial system application, research was previously carriedout using a system development life cycle (SDLC) approach. In the application of the stock and financialsystem, research objects, interviews and field research are used as the basis for system performance.Multiuser based stock and financial system application is designed using Visual Basic 6.0 programminglanguage and uses MySQL database.